2020
DOI: 10.1186/s43042-020-00078-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glutathione S-transferase polymorphism in Iranian patients with type 2 diabetic microangiopathy

Abstract: Background: Overproduction of reactive oxygen species as a result of hyperglycemia in diabetes mellitus leads to microvascular complications. Glutathione S-transferases play important detoxifying roles with antioxidant potentials. This study aimed to assess whether the glutathione S-transferase M1 and T1 genotypes were associated with type 2 diabetes mellitus microangiopathic complications in the Iranian population. Results: In this case-control study, the frequencies of null GSTM1 and GSTT1 genotypes were 4/7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…We conducted this subanalysis to reduce the potential arbitrariness. Three studies [ 18 , 40 , 44 ] had both healthy controls and selected controls. Data synthesis of these studies was recalculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted this subanalysis to reduce the potential arbitrariness. Three studies [ 18 , 40 , 44 ] had both healthy controls and selected controls. Data synthesis of these studies was recalculated.…”
Section: Resultsmentioning
confidence: 99%
“…Deletions of GSTM1 and GSTT1 result in a lack of enzyme activities, and the G allele of GSTP1 (rs1695, p. Ile105Val) reduces its enzymatic activity by 50%–70 % compared to the wild-type [ [11] , [12] , [13] , [14] ]. Many case‒control studies have been reported, and some of them showed significant associations between GST polymorphisms and CKD risk [ 10 , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ]. To extend our prospective study, this study was warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been reported to be an important risk factor for the initiation and progression of diabetic complications. 20 …”
Section: Discussionmentioning
confidence: 99%
“…As the oxidative stress increased the formation of free radicals and the weakening of the free radical inhibitors and scavengers would in turn, increase the oxidative stress leading to cell damage and death [36]. Regarding to the study by Mohammad Bagher Hashemi-Soteh et al [37] the GSTT1null genotype was considerably more common in diabetic neuropathy patients than in nonneuropathic individuals. The involvement of the GSTT1-null genotype in predisposing patients with T2DM was a higher risk factor for diabetic neuropathy.…”
Section: Ihjpas 5 3 (4)2022mentioning
confidence: 97%